An Open-Label, Multicentre Pilot Study of Bosentan in Pulmonary Arterial Hypertension Related to Congenital Heart Disease. Issue 8 (2006) - Ibrahim, Reda; Granton, John T; Mehta, Sanjay
Abstract : BACKGROUND: Bosentan has been shown to be a safe and efficacious treatment for idiopathic pulmonary arterial hypertension (PAH) and PAH associated with connective tissue disease. However, there are limited studies examining the benefits of bosentan in PAH associated with congenital heart disease (CHD). OBJECTIVE: The aim of the present pilot study was to explore the safety and efficacy of bosentan in patients with PAH associated with CHD. PATIENTS AND METHODS: In the present study, 11 patients with PAH associated with CHD were enrolled to receive bosentan for a minimum of 16 weeks (62.5 mg twice a day for four weeks; thereafter 125 mg twice a day). Safety was assessed by monitoring adverse events, oxygen saturation, systemic blood pressure, pulse, complete blood count and liver function tests. Efficacy was assessed by the World Health Organization functional class, 6 min walk test (6-MWT), modified Borg dyspnea index, echocardiography and the 36-item short form health survey. RESULTS: Ten patients completed the 16-week treatment period (one patient withdrew). Bosentan was not associated with a deterioration in resting oxygen saturation (83.0±4.6% at week 16 versus 81.9±6.1% at baseline; P=0.402), or a deterioration in post-6-MWT oxygen saturation (70.1±10.9% at week 16 versus 68.7±15.1% at baseline; P=0.747). Two patients experienced three serious adverse events. The distance walked in 6 min improved significantly by 28 m (P=0.005) at week 16 compared with baseline, and the modified Borg dyspnea index also improved at week 16 compared with baseline (P=0.050). The World Health Organization functional class improved from class III to class II for five of 10 patients (50%). Patients' self-rated quality of life (36-item short form health survey) demonstrated a non-significant improvement in each of the eight domains. Obtaining reliable echocardiographic measurements was difficult. Most echocardiographic parameters were only measurable on few patients, and none were measured on all patients, questioning the usefulness of echocardiography as a measuring tool for patients with complex CHD. CONCLUSION: Bosentan was not associated with worsening of resting oxygen saturation or exercise systemic oxygen saturation, suggesting its potential as a safe treatment option for patients with PAH associated with CHD. Improved 6-MWT and the modified Borg dyspnea index also suggested the possibility of bosentan as an efficacious treatment option for these patients. The results of the present study provide evidence for the need and feasibility of a large randomized, placebo-controlled clinical trial.